Diclofenac and Omeprazole Electrochemical Determination on Cobalt (III) Oxyhydroxide-Modified Electrode. A Theoretical Study - Tkach, V. V.; Kushnir, M. V.; de Oliveira, S. C.; Ivanushko, Y. G.; Kryvetskyi, V. V.; Kryvetska, I. I.; Kryvetskyi, I. V.; Banul, B. Yu.; Honchar, T. V.; Yagodynets', P. I.; da Silva, Adriano O.; Derevianko, N. P.; et al. (My University, 2024)
The theoretical description for diclofenac, and omeprazole electrochemical determination over CoO(OH)-modified electrode has been described. In a basic solution, phenolization and hydrolysis occur, and the solution is provided by cobalt (III) oxyhydroxide-based hydroxyl transfer. In the basic medium, the ionization degree of the analyte and its oxidation products is high, which enhances the probability of the oscillatory behavior. Also, the reaction mechanism may become branched, as both analytes tend to be oxidized by a hybrid mechanism, including parallel scenarios. The scenario becomes even more differentiated if the redox pair CoO(OH)/CoO2 is used. Either way, the electrochemical determination of omeprazole and diclofenac on cobalt (III) oxyhydroxide may be efficient from the electroanalytical point of view.
Keywords: diclofenac; omeprazole; cobalt (III) oxyhydroxide; electrochemical sensors; stable steady-state